2017
DOI: 10.1186/s12935-017-0424-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth of MCF-7 breast cancer cells and efficacy of anti-angiogenic agents in a hydroxyethyl chitosan/glycidyl methacrylate hydrogel

Abstract: BackgroundBreast cancer negatively affects women’s health worldwide. The tumour microenvironment plays a critical role in tumour initiation, proliferation, and metastasis. Cancer cells are traditionally grown in two-dimensional (2D) cultures as monolayers on a flat solid surface lacking cell–cell and cell–matrix interactions. These experimental conditions deviate from the clinical situation. Improved experimental systems that can mimic the in vivo situation are required to discover new therapies, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The cells were counted using a trypan blue exclusion method in hemocytometer. 29 Cell viability assay ER + MCF-7 cells (1 Â 10 5 ) were seeded in 96-well sterile plates and treated with different concentrations of BBAP-1 (1 mM, 5 mM, 10 mM, 15 mM, 20 mM, 25 mM) for 24 h against control and standard drug (tamoxifen). Aer 24 h of incubation at 37 C in an atmosphere of 5% CO 2 and 95% humidity, the apical and basolateral media were pooled on a 24-well plate and the cell viability was estimated by MTT assay through measuring the emitted uorescence with a spectrouorometric multi plate reader (excitation-555 nm, emission-585 nm).…”
Section: Metabolic Proling Of Bbap-1mentioning
confidence: 99%
“…The cells were counted using a trypan blue exclusion method in hemocytometer. 29 Cell viability assay ER + MCF-7 cells (1 Â 10 5 ) were seeded in 96-well sterile plates and treated with different concentrations of BBAP-1 (1 mM, 5 mM, 10 mM, 15 mM, 20 mM, 25 mM) for 24 h against control and standard drug (tamoxifen). Aer 24 h of incubation at 37 C in an atmosphere of 5% CO 2 and 95% humidity, the apical and basolateral media were pooled on a 24-well plate and the cell viability was estimated by MTT assay through measuring the emitted uorescence with a spectrouorometric multi plate reader (excitation-555 nm, emission-585 nm).…”
Section: Metabolic Proling Of Bbap-1mentioning
confidence: 99%
“…The results showed a malignant phenotype in tumors created by the 3D cultured cells. Migration, cell growth, and tumor volume were higher in the 3D group 37 . In the present study, the creation of 3D model was different from previous studies in that 1 × 10 6 4 T1 cells (mouse breast cancer), after being harvested from 2D culture medium, was loaded in the hydrogel, and was injected into the flank of mice and the same number of cells were injected into the mice without hydrogel.…”
Section: Discussionmentioning
confidence: 65%
“…Migration, cell growth, and tumor volume were higher in the 3D group. 37 In the present study, the creation of 3D model was different from previous studies in that 1 × field. 38,39 Ultrasound examination of various types of human breast tumors revealed that the malignant tumor tissue is hyperecogenic, darker in sonography, and have higher tissue density, while benign tissue is hyperecogenic and its connective tissue and fat content is higher.…”
Section: Discussionmentioning
confidence: 69%
“…This is similar to the morphologies of healthy MCF‐7 cells seen in previous works. [ 59 ] Cells in the presence of neat FLS assemblies (without drug, Figure S6b, Supporting Information) showed aggregation and appearance of ribbon‐like membrane ruffles upon adhesion to the assemblies. In previous studies, it has been reported that MCF‐7 cells, when treated with certain small molecules or drugs such as tamoxifen showed E‐cadherin‐dependent ability to form aggregates which in turn reduced invasive behavior, as MCF‐7/6 displays inverse relation between aggregation and invasion.…”
Section: Resultsmentioning
confidence: 99%